EXPERIMENTAL RESEARCH OF A MULTISTAGE GRAVITATIONAL CLASSIFIER - Leudanski Aliaksandr Eduardovich,; Chirkun Dmitrii Ivanovich,; Golubev Vladmir Grigorevich,; Sarsenbekuly Didar,; Zhumadullayev Daulet Koshkarovich, (Academic Scientific Journal of Chemistry, 2020)
The classification of polydisperse materials is widely used in many industries. Of the wide range of classification equipment, the most promising are multistage gravitational classifiers. The classification process in multistage gravitational classifiers is quite complicated and requires the necessary experimental research to ensure the given efficiency. To receive reliable information allowing to obtain the most effective recommendations for their structure and use, a set of experimental research was carried out. The research results showed that multistage classifiers of small sizes provide a consistently high quality of separation, however their performance, for an apparatus with a cross section of 80x80 mm no more than 100 kg/h, is insignificant, as a result of which they cannot be used for most production processes. Classifiers with higher performance must have significant sizes. It is advisable to use multistage shelf classifiers with boundary separation sizes of 0.5-2 mm. With a boundary size of less than 0.5 mm, a steady decrease in the separation efficiency is observed, and with a boundary size of the order of 0.05-0.1 mm, the classification efficiency decreases sharply. With an increase in the boundary separation grain of more than 2 mm, a decrease in the classification efficiency is also observed (figure 1). The experiments to determine the separation efficiency in the modernized and conventional structures of classifiers in the separation of quartz sand with particle sizes of 0-2 mm relative to the boundary separation size of гр = 1 mm showed the following. The mutual arrangement of the efficiency curves shows that an increase in the separation efficiency for the modernized classifier is up to 10% when the optimum, providing the highest quality separation, air velocity per section of the apparatus is achieved. Similar results were obtained for other materials (sylvinite, meal, gypsum) for various boundary separation sizes (from 0.5 to 2 mm). In general, the separation efficiency in the modernized structure of the shelf classifier for various materials was 5-10% higher than in a conventional one. The experimental research of the modernized classifier structure showed that the proposed structural additions, ceteris paribus, contribute to a more uniform distribution of material over the working volume of the apparatus, which, of course, leads to an increase in the quality of separation.